Airlines and the COVID-19 Pandemic - McCarthy, Patrick S. (Emerald Publishing, 2025)
Airlines and the COVID-19 Pandemicassesses the pandemic's diverse impacts on the aviation sector, how airlines reacted to the pandemic, worked with governments, and adapted its operations and business models.
Keywords: Aufsatzsammlung